Minimally invasive percutaneous endoscopic foraminotomy and discectomy in a French Bulldog with intervertebral disc extrusion - Krajarngjang, Tanhatai; Limpongsai, Luksamee; Darapong, Panutda; Sonbanpai, Woraphanit; Taweechart, Mataya (The Thai Journal of Veterinary Medicine, 2026)
A six-year-old female French Bulldog was referred for neurological diagnostic tests and treatment for progressive paraparesis over an 8-day period. The dog had a history of intervertebral disc extrusion (IVDE) surgical correction two years prior. Neurological examination revealed T3–L3 myelopathy. Magnetic resonance imaging of the thoracolumbar spine confirmed IVDE with spinal cord compression at T13–L1. A minimally invasive percutaneous endoscopic foraminotomy and discectomy (PEFD) was performed to remove the extruded disc material. The patient regained the ability to stand and showed voluntary limb movement 48 hours post-surgery. At the 4-week follow-up, the patient showed a complete recovery to her baseline neurological status. No complications were reported. Beyond a smaller incision, minimally invasive spinal surgery (MISS) offers advantages, including reduced muscular trauma, minimal blood loss, and decreased postoperative pain. Furthermore, the magnification and illumination provided by MISS offer superior visualization compared to conventional open surgery, presenting an advantage for procedures in delicate areas requiring high precision.